The burden and etiologies of diarrhea in Asia and its countries from 1990 to 2021 and the forecast to 2040: analyses informed by the global burden of disease study 2021 - Liu, Shan; Wu, Zhiping; An, Qingyu; Wu, Jun; Bai, Jinjian; Sun, Wei; Guo, Linan; Gong, Luxi (Frontiers in Public Health, 2025)
BackgroundThis study aimed to analyze the burden, temporal trends and etiologies of diarrhea from 1990 to 2021, and to forecast the burden from 2022 to 2040 in Asia and Asian countries.MethodsData were sourced from the Global Burden of Diseases (GBD) 2021 study. Temporal trends from 1990 to 2021 were analyzed using estimated annual percentage change (EAPC) values. Spearman’s rank test was performed to evaluate the association between diarrhea burdens and socio-demographic index (SDI). Joinpoint analysis was applied to estimate the trends of age-standardized rates (ASRs) from 1990 to 2021. To forecast the burden for diarrhea from 2022 to 2040, we used Bayesian Age-Period-Cohort (BAPC) model. Furthermore, we generated heatmaps to visualize the 13 etiologies of diarrhea.ResultsOverall burden showed that the ASRs in Asia decreased from 1990 to 2021, with EAPCs of −0.40, −0.55, −5.70, and −5.47, respectively. The ASRs demonstrated statistically significant negative correlations with SDI in 2021. The incidence and prevalence rates in 0–9 years old and 90+ years old and the DALY rates and mortality rates in all age groups in 2021 were decreased compared with 1990. Temporal joinpoint analysis revealed that after 2019, the age-standardized incidence rate (ASIR) of diarrhea exhibited a significant upward trend in Asia and some Asian countries. Based on the BAPC model analysis, the ASIR and the age-standardized prevalence rate of diarrhea in Asia are predicted to decrease initially and then increase. The age-standardized DALY rate (ASDR) and the age-standardized mortality rate (ASMR) of diarrhea in Asia are predicted to demonstrate a consistent declining trend. Rotavirus showed the highest ASDRs in both 1990 and 2021 among 13 diarrheal etiologies, while norovirus replaced rotavirus as the leading cause of ASMR by 2021.ConclusionThe study demonstrates an overall declining trend in the burden of diarrhea in Asia due to urbanization, economic growth, and public health interventions. However, significant challenges persist in some countries and specific population groups. Socioeconomic status exerts a substantial influence on disease burden, highlighting the urgent need for enhanced healthcare resource allocation in some countries.